Social Legitimacy versus State Legal Certainty: The Dialectics of Kiai Marriages as Living Law in Dusun Pondok Asem, Kertasemaya, Indramayu - Lulu Ul Jannah; Inna Fauziatal Ngazizah; Abdurrohman Kasdi (Al-Mazaahib: Jurnal Perbandingan Hukum, 2025)
The practice of unregistered marriages in the tradition of kiai marriages in Dusun Pondok Asem, Kertasemaya Subdistrict, Indramayu Regency, is still rampant even though marriage regulations have been strictly regulated through Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). This phenomenon shows the gap between state law and local traditions that continue to be practiced by the local community. This study aims to describe the legal status of Kiai marriage according to customary law and state law, compare the recognition of both, and show the implications of legal pluralism in marriage practices in Indonesia. This research uses a juridical-empirical approach with a theoretical framework for legal pluralism. Primary data was obtained through interviews with lebe, traditional leaders, village officials, and kiai marriage practitioners, while secondary data was obtained from legislation, KHI, and related academic literature. The analysis was conducted qualitatively using a comparative model between customary and state law. The results of the study show the existence of dualism in recognition. Customary law recognizes Kiai marriages as valid because they fulfill the requirements of Islamic marriage and obtain social legitimacy, so that children born from these marriages receive full recognition. Conversely, state law does not recognize marriages not officially registered at the Office of Religious Affairs, so these marriages do not have strong legal force. The novelty of this research lies in its attempt to reveal the dialectic between social legitimacy as living law and formal legal certainty as the main principle of state law. This dialectic shows the reality of legal pluralism in Indonesia, emphasizing the need for harmonization so that customary law and state law can work more synergistically.  Praktik nikah siri dalam tradisi kawin kiai di Dusun Pondok Asem, Kecamatan Kertasemaya, Kabupaten Indramayu masih marak dilakukan meskipun regulasi perkawinan telah diatur secara tegas melalui Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Kompilasi Hukum Islam (KHI). Fenomena ini menunjukkan adanya jarak antara ketentuan hukum negara dan tradisi lokal yang tetap dijalankan masyarakat setempat. Penelitian ini bertujuan untuk mendeskripsikan status hukum kawin kiai menurut hukum adat dan hukum negara, membandingkan pengakuan keduanya, serta menunjukkan implikasi pluralisme hukum dalam praktik perkawinan di Indonesia. Metode penelitian menggunakan pendekatan yuridis-empiris dengan kerangka teori pluralisme hukum. Data primer diperoleh melalui wawancara dengan lebe, tokoh adat, aparat desa, dan pelaku kawin kiai, sedangkan data sekunder berasal dari peraturan perundang-undangan, KHI, serta literatur akademik terkait. Analisis dilakukan secara kualitatif dengan model komparasi antara hukum adat dan hukum negara. Hasil penelitian menunjukkan adanya dualisme pengakuan. Hukum adat mengakui kawin kiai sebagai sah karena memenuhi rukun nikah Islam dan memperoleh legitimasi sosial, sehingga anak hasil perkawinan mendapatkan pengakuan penuh. Sebaliknya, hukum negara tidak mengakui perkawinan yang tidak tercatat resmi di Kantor Urusan Agama, sehingga perkawinan tersebut tidak memiliki kekuatan hukum yang kuat. Kebaruan penelitian ini terletak pada upaya menyingkap dialektika antara legitimasi sosial sebagai living law dan kepastian hukum formal yang menjadi prinsip utama hukum negara. Dialektika ini memperlihatkan realitas pluralisme hukum di Indonesia, sekaligus menegaskan perlunya harmonisasi agar hukum adat dan hukum negara dapat berjalan lebih sinergis.